Bone Disruption and Environmental Pollutants - Giannattasio, Raffaele; Lisco, Giuseppe; Giagulli, Vito A.; Settembrini, Silvio; De Pergola, Giovanni; Guastamacchia, Edoardo; Lombardi, Gaetano; Triggiani, Vincenzo (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Background: Endocrine Disrupting Chemicals (EDCs) are ubiquitous and may significantly contribute to environmental pollution and contamination in humans and wildlife. Ecological pollutants could interfere with bone homeostasis through different mechanisms, including hormonal imbalance, direct osteoblast toxicity, and enhancement of osteoclasts activity, leading to either osteopenia or osteoporosis. Among these chemicals, bisphenols, dioxins, polycyclic aromatic hydrocarbons, polychlorobiphenyls, poly- and perfluoroalkyl, phthalates, parabens, organotins, and cadmium may play a role in the bone disruption. Methods: Authors searched PubMed/MEDLINE, ISI-web of knowledge, and Google scholar databases for medical subject headings terms and free-text words related to the classes mentioned above of chemicals and bone metabolism and remodeling for better clarifying and understanding the main mechanisms of bone disruption. Results: Several EDCs act as xeno-estrogens. Considering that estrogens play a significant role in regulating bone remodeling, most of these chemicals generate hormonal imbalance with possible detrimental consequences on bone tissue structure and its mechanical and non-mechanical properties. Discussion: Much evidence about bone disruptors was obtained from in vitro studies or animal models with equivocal results. Besides, a few data have been acquired from humans, and most of these data focused on the impact of EDCs on bone mineral density without considering their influence on long-term fracture risk. Moreover, humans may be exposed to a mixture of EDCs, and the final effect on bone metabolism might be attributable to either synergistic or antagonist effects. Age of first exposure, cumulative exposure over time, and the usually observed non-monotonic dose-response curve for EDCs should be considered as other essential variables influencing bone metabolism's final effect. Conclusion: Given these variables, observational studies are needed to analyze this issue for ecological purposes better and preserve bone health.
Keywords: Endocrine-disrupting chemicals